1,2,3-Triazoles and their metal chelates with antimicrobial activity - Todorov, Lozan; Kostova, Irena (Frontiers in Chemistry, 2023)
The emergence of drug-resistant bacterial and fungal pathogens has highlighted the urgent need of innovative antimicrobial therapeutics. Transition metal complexes with biologically active ligands (coumarins, terpyridines, triazoles, uracils, etc.) have long been investigated for antimicrobial activity. 1,2,3-Triazoles and their molecular derivatives are well known for a plethora of physiological activities, including antibacterial and antifungal. The aim of the present mini-review is to inform the reader about research conducted on potential antimicrobial 1,2,3-triazole complexes with transition metals. What the authors find surprising is how little such research and experimentation has actually been performed and reported in scientific literature. The goal is to highlight research efforts up to now and impress upon the reader the vast perspectives for novel, effective medicinal substances hidden in this yet unexplored field.